Quality of Life Assessment of Breast Cancer Patients Undergoing Chemotherapy in Jordan: A Cross-Sectional Study - Sijood Janabi; Lobna Gharaibeh; Ibrahim Aldeeb; Ali Abuhaliema (International Journal of Breast Cancer)
Conclusion: The results of the study showed the impact of chemotherapy on the lives of patients and highlighted the aspects that need greater focus by healthcare providers in Jordan. In addition to providing treatment, emotional and psychological support are necessary to improve the quality of life for these women.